Results of Mentoring in the Psychosocial Well-Being of Young Immigrants and Refugees in Spain - Sánchez-Aragón, Anna (Healthcare (Basel), 2020)
This study examined the change processes associated with the Nightingale project, a community-based mentoring programme whose aim is to promote the social inclusion of minors of immigrant origin. A pre-test–post-test study was conducted on a group of 158 young immigrants between the ages of 8 and 15, in which the influence of the mentoring programme on the youths’ psychosocial well-being was measured. Non-parametric tests were used to calculate the results before and after mentoring, comparing the results over a six-month period and controlling for sex and age. The analyses reflected associations between mentoring and improvements in specific aspects of the emotional well-being of young immigrants and highlighted the potential of mentorships to cushion the stressful events they are subjected to in the process of adapting to a new social reality.